Immune profiling in patients with recurrent miscarriage - Kuon, Ruben-Jeremias; Strowitzki, Thomas; Sohn, Christof; Daniel, Volker; Toth, Bettina (Journal of reproductive immunology, 2015)
The central role of the maternal immune system for successful and disturbed pregnancies such as recurrent miscarriage (RM) is apparent. Recent studies have increased understanding of the complex interaction of the different immunological players and the adaptation of the maternal immune system to the semi-allogeneic embryo. There is growing evidence for immunological abnormalities in RM patients, including autoimmune and allogeneic factors. However, the question remains unsolved whether these changes represent the cause or the consequence of RM. As in half of the RM patients the underlying mechanism remains unknown, further diagnostic methods are urgently needed. Within this review we summarize (recent) literature on the immunological diagnosis in RM patients to find out current trends and to identify potential targets of therapy. As the exact mechanisms of feto-maternal tolerance have not yet been determined we suggest that the immunological diagnosis should be implemented only in well-designed clinical trials in specialized centers to establish a standardized immunological work-up in RM patients.
Gesehen am 19.07.2017